Detection of Beef Type Dark, Firm, and Dry (DFD) and Pale, Soft, and Exudative (PSE) for Sale at Peunayong Market Banda Aceh - Andi Novita Novita; Silvia Rahman Siregar; Teuku Reza Ferasyi (The Faculty of Veterinary Medicine of Syiah Kuala University, 2021)
This study aims to determine beef types Dark, Firm, and Dry (DFD) and Pale, Soft, and Exudative (PSE) that are sold at the Peunayong Market, Banda Aceh. A total of nine samples of beef from different sellers will be used as extracts and the pH is measured three times every 1 hour for 12 hours to determine the trend of decreasing pH. Organoleptic observations were carried out to determine the visual differences shown by the meat samples. Parameters observed were meat color, meat aroma, meat texture and surface state of the meat. The data obtained from pH measurements and organoleptic tests were analyzed descriptively. Based on the results of pH measurements seen from the decreasing trend of pH in nine samples of beef, seven of them were PSE type beef with a pH value of 5.2 and the other two samples were of good quality meat with a pH value ranging from 5.6 to 5.4. From the results of organoleptic tests for color parameters, four samples were pale, one sample was very pale and the rest were red. All the meat samples tasted normal. Meat texture and surface condition for soft-textured meat has a wet surface, while hard-textured meat has a dry surface.